Modern Pension Provision System as a Social Insurance Program - Rafael Y. Rakhmatullin, Rail R. Uraev, Venera F. Yunusbaeva,; Shaidukova, Liana D.; Semenova, Elvira R.; Aleksandr M. Rudakov, Albina R. Valieva, Zulfiya R. Mingazova, Liliya F. Zaynetdinova, (Opción, 2019)
The article presents the results of the author's empirical research that isthe expert survey of employees of different management levels in thefield of the regional pension provision system via a systematicapproach, the essence of which is to present the object of study as asystem. As a result, the author gives the definition for the notionpension provision system as a social insurance program. There are also  main characteristics of Russian pension provision programs. In conclusion, pension provision system is a collective work of different social institutions